The Effect of Fiscal Decentralization to Gross Domestic Regional Product of District / City in South Sumatra Province - Dessy Dian Syari; Syamsurijal Syamsurijal; Bernadette Robiani (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
This study aims to examine the effect of fiscal decentralization on gross regional domestic product (GRDP) of districts in South Sumatera. The data used in this study are secondary data in the form of GRDP, district expenditure to provincial expenditure ratio, district revenue to district expenditure ratio and balancing fund to district revenue ratio in 15 districts/cities in South Sumatera for 11 years during the period of 2005-2015. Multiple regression analysis on fixed effect model is used in analyzing the data. The result shows that simultaneosly, fiscal decentralisation has significant effect on GRDP of districits/cities in South Sumatera. However, in partial test, the district expenditure to provincial expenditure ratio is positive and insignificant. This is related to the district expenditure allocation that has not any direct impact on the district economy thus, it has yet to give results that can support the economic growth.